2019
DOI: 10.1186/s12890-019-0936-1
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic ultrasound findings correlate with dyspnea, exercise tolerance, health-related quality of life and lung function in patients with fibrotic interstitial lung disease

Abstract: Background Fibrotic interstitial lung disease (FILD) patients are typically dyspneic and exercise-intolerant with consequent impairment of health-related quality of life (HRQoL). Respiratory muscle dysfunction is among the underlying mechanisms of dyspnea and exercise intolerance in FILD but may be difficult to diagnose. Using ultrasound, we compared diaphragmatic mobility and thickening in FILD cases and healthy controls and correlated these findings with dyspnea, exercise tolerance, HRQoL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
55
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 56 publications
(80 reference statements)
9
55
1
2
Order By: Relevance
“…Reduced DB diaphragmatic mobility correlated with lung function. 78 - 80 2. Increased Tdi-exp is an effect of training of the diaphragm.…”
Section: Diaphragmatic Ultrasound In Respiratory Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Reduced DB diaphragmatic mobility correlated with lung function. 78 - 80 2. Increased Tdi-exp is an effect of training of the diaphragm.…”
Section: Diaphragmatic Ultrasound In Respiratory Diseasesmentioning
confidence: 99%
“…Increased Tdi-exp is an effect of training of the diaphragm. 78 , 80 3. Reduced mobility and thickening during DB correlated positively with lung function, exercise tolerance, and HRQoL, correlating negatively with dyspnea.…”
Section: Diaphragmatic Ultrasound In Respiratory Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…These correlations were influenced by sex, being diaphragm mobility during deep breathing more significantly correlated with female sex, whereas the thickening fraction of the diaphragm correlated more with the male sex [25]. In lung interstitial disease, another study revealed that diaphragmatic mobility correlated with interstitial lung disease functional severity, and an FVC% cut-off value of < 60% was found to be highly accurate for identifying diaphragmatic dysfunction on the US [26]. In patients with various neuromuscular disorders (amyotrophic lateral sclerosis, myopathy and neuropathy), there was a significant correlation between diaphragm thickness determined by US and FVC determined by spirometry.…”
Section: Introductionmentioning
confidence: 99%